Sustainable finance: exploring the frontiers of current research / Hairul Suhaimi Nahar, Maslinawati Mohamad and Noor Raida Abd Rahman - Nahar, Hairul Suhaimi; Mohamad, Maslinawati; Abd Rahman, Noor Raida (UiTM Press, 2023)
This study explored the frontiers of current sustainable finance (SF) research by identifying research traits, important in shaping its future research direction. It combined analytical techniques covering bibliometrics, citation, social networks, and the content analysis of 690 papers published in the Scopus database between 1979 and 2021 (43 years). The analytical results suggested that SF has grown into a cross-disciplinary research area where past literature had concentrated mainly on business-related and environmental science domains. The three primary areas of focus in sustainable finance that have received considerable attention from scholars over the past few years include microfinance, green finance, and green banking. The publishing trend was first fragmented but ramped up post-2005 and further spiked post-2015, primarily due to the United Nations' establishment and propagation of Sustainable Development Goals (SDGs), which systematically caused the literature to proliferate, covering more strategic research issues. The paper contributes to SF's existing body of knowledge by highlighting critical research properties and suggesting ten promising areas important for early and/or matured researchers in framing their future research trajectory involving SF.